Cultural Intelligence and the Populist Discourse Manifested through Social Media - Frunză, Sandu (Journal for the study of religions and ideologies, 2024)
Social media is a part of our everyday reality. Therefore, the ethical and legal tendency to identify a virtual space as a public space is not at all surprising. Social media represents the most accessible public space, with a democratic type of access, open to individuals coming from an infinite variety of cultural spaces, all connected to the space of global communication. It is natural that an appetence for the political game is developed throughout participants, aiming at the accession and the transmission of messages and at the formation of an ideological community, molded into groups of support and broadcast for the ideas promoted. Regarding this matter, the presence on social media of niche political movements, of populist groups, of everyone counting on the impact the virtual world has over the people these categories are targeting. Merging the ideological imaginary with the religious one is an ordinary practice when it comes to the leaders and supporters of populist networks. In this context, there are several elements emphasized in the paper, specific to the populist discourse found in the Romanian cultural space, discursively manifested through the communication happening in the virtual space. In a world of global communication, we have been interested in an analysis of populist discourse which proposes a rejection and a demonization of alterity, using means that are specific to religious ideologies, suggesting as possible antidote the use of cultural intelligence as an instrument of intervention in relation to the process of shaping the individual and collective mental state.